Bitemark evidence: a color atlas and text - Dorion, Robert B.J (CRC Press, 2011)
Experts in the field of bitemark evidence confront complexities ranging from the identification and collection of evidence, to microscopic analysis, to legal implications and courtroom admissibility. Now in its second edition, Bitemark Evidence reflects the knowledge, training, experience, opinions, and research of 27 authors from around the world